INTERNALISASI NILAI-NILAI RELIGIUS DALAM PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 1 MANGARAN SITUBONDO - Chairul Imam; Nur Hasan; Rosichin Mansur (VICRATINA, 2021)
This study discusses the internalization of religious values in the learning process ofIslamic Religious Education at SMPN 1 Mangaran Situbondo which is carried outthrough extra-curricular Islamic Spirituality. The purpose of this internalization is toform the Muslim personality of students at SMPN 1 Mangaran Situbondo. Thisresearch includes descriptive qualitative research, because the researcher tries toexplain the Internalization of Religious Values in the Learning Process of IslamicReligious Education at SMPN 1 Mangaran Situbondo. Therefore, this research isexpected to be able to reveal various information that occurs in the field which issupported by the data that has been obtained. So that researchers can analyze whichcan then be concluded as the final result of the study.